Monitoring socio-climatic interactions to prioritise drinking water interventions in rural Africa - Armstrong, A; Hope, R; Munday, C (Springer Nature, 2021)
Rainfall variability and socioeconomic shocks pose a revenue risk for drinking water services in rural Africa. We examine the year-on-year and seasonal relationship between rainfall and remotely monitored water usage from rural piped schemes in four sub-Saharan countries to identify patterns that warn of a threat to operational sustainability. Continuous monitoring of socio-climatic interactions can reveal distributions and magnitudes of risk and guide policy action to safeguard rural water services.